Potential serum biomarkers associated with mild and severe leptospirosis infection: A cohort study in the Malaysian population. Issue 17 (8th June 2017) - Tan, Xue Ting; Amran, Fairuz binti; Thayan, Ravindran; Ahmad, Norazah; Jaafar, Roslinda; Haron, Rahimah; Abdullah, Rafidah; bin Shamsuddin, Sazwan Reezal; Md. Riffin, Nor Suhaila binti; Abdul‐Rahman, Puteri Shafinaz
Abstract: Leptospirosis is an emerging zoonotic infectious disease in Malaysia. The symptoms of leptospirosis vary from mild nonspecific flu‐like illness to a severe condition which is usually associated with serious complication and fatality. To study the protein expression profile of mild and severe leptospirosis, 15 paired sera were collected from the patients who were mildly infected and following that progressed to severe stage. The proteome profiles of mild and severe cases were studied using 2DE analysis in combination with LC‐MS/MS. The expression of proteins that were significantly different and had a fold difference of at least 2 had been identified and then validated using Western blot. Our study demonstrated apolipoprotein A‐I (APOA‐I), serum amyloid A (SAA), transferrin (TF), haptoglobin (HP) and transthyretin (TTR) have significantly different expression between mild and severe leptospirosis. The Ingenuity Pathway Analysis software suggested the expression of these five proteins were modulated by acute phase response signaling pathway. Besides that, a functional network of lipid metabolism, molecular transport and small molecule biochemistry that interconnects these five proteins with interactomes also had been predicted by this software. In conclusion, this finding supports the potential of these five proteins to be the biomarkers for mild and severe human leptospirosis.